E-124 Persistent TICI 0 after mechanical thrombectomy: incidence and insights at a high-volume comprehensive stroke center. (22nd July 2019) - Mattay, R; Cox, M; McCabe, M; Schmitt, J; Kung, D; Choudhri, O; Pukenas, B; Hurst, R
Abstract : Purpose: There is now class 1a evidence for the efficacy of mechanical thrombectomy in patients with acute ischemic stroke and a large vessel occlusion (LVO). 1 2 Failure to recanalize portends a poor prognosis for the patient with a decreased chance for a good function outcome (modified Rankin Score of 2 or less). The purpose of our study was to evaluate the incidence and causes of persistent occlusion of intracranial large vessel occlusion following mechanical thrombectomy at our high-volume comprehensive stroke center, with the goal of providing some insight into potential ways to increase recanalization rates in future patients. Methods: After institutional board approval, a prospectively maintained institutional thrombectomy database for acute ischemic stroke was queried from 2015 to present. Patients with documented large vessel occlusion in the intracranial circulation and failure to recanalize after attempted mechanical thrombectomy were included for analysis. Patient characteristics including age, sex, co-morbidities, baseline NIHSS score, and baseline ASPECTS, were recorded. Rates of symptomatic hemorrhage, final ASPECTS, need for decompressive hemicraniectomy, and outcomes at 90 days (modified Rankin Scale) were also included. The statistical package R was used for analysis. Results: 24 out of 368 patients with LVO and acute ischemic stroke had persistent TICI 0 occlusions after attempted mechanical thrombectomy. 15 patients were male. Mean age of patients with persistent TICI 0 was 68.8 years (range 44 to 94 years). A combination of stent-retrievers and direct aspiration (solumbra) was used for mechanical thrombectomy in all cases were the lesion was accessible. The most common reason for persistent TICI 0 was failure to recanalize despite adequate stent apposition and aspiration, which occurred in 18 out of 24 cases, or 75% of cases. Inability to pass a microwire through the site of occlusion was the second most common reason for persistent TICI 0, which occurred in 5 out of 24 of cases (21%). Inability to select the proximal great vessels due to extreme tortuosity only occurred in one case. 11 out of the 24 patients with persistent TICI 0 occlusions died within 90 days of attempted thrombectomy. Conclusions: The rate of TICI 0 mechanical thrombectomy was extremely low in our series, accounting for only 7% of thrombectomy cases at our high-volume stroke center. Failure to recanalize the site of large vessel occlusion was the most common reason for persistent TICI 0 after attempted mechanical thrombectomy in our large series, occurring in 75% of persistent TICI 0 cases. In our series, persistent TICI 0 after mechanical thrombectomy had a high mortality rate, nearly 50%. References: Berkhemer OA, Fransen PS, Beumer D, van den Berg LA, Lingsma HF, Yoo AJ, et al. A randomized trial of intraarterial treatment for acute ischemic stroke. N Engl J Med 2015;372(1):11–20. Goyal M, Demchuk AM, Menon BK, Eesa M, Rempel JL, Thornton J, et al. Randomized assessment of rapid endovascular treatment of ischemic stroke. N Engl J Med 2015;372(11):1019–30. Disclosures: R. Mattay: None. M. Cox: None. M. McCabe: None. J. Schmitt: None. D. Kung: None. O. Choudhri: None. B. Pukenas: 2; C; Regenxbio, Prevail Therapeutics. R. Hurst: None.